The impact of global geopolitical risk on Afghanistan's economic condition: Evidence from wavelet quantile regression - Pooya, Abdul Ahmad (Journal of Economics and Business Letters, 2025)
This study explores the dynamic effects of global geopolitical risk (GPR) on Afghanistan's macroeconomic performance using data from 1990 to 2024. The results of Wavelet Quantile Regression (WQR) show that GPR shocks have immediate and negative impacts on GDP, the Exchange Rate (EXP), imports (IMP), exports (EXP), and inflation (INF) across all quantiles in the short, medium, and long terms. Notably, the response of GDP per capita to GPR is strong in the short term but diminents over time. Additionally, IMP and EXP are negatively affected by GPR dynamics owing to border closures, sanctions, and disruptions to trade routes in both the short and long terms. The most significant vulnerabilities are revealed in EXP and INF, where persistent depreciation and unstable prices harm household welfare in low-income, import-dependent economies. These findings provide new insights into one of the most fragile nations within the global system and demonstrate the role of the WQR in breaking down multi-scale dynamics often overlooked by linear models. This study underscores the urgent need for Afghanistan to develop adaptation policies that can mitigate short-term shocks, build external buffers, and enable structural reforms, ultimately making the country less vulnerable to long-term geopolitical shocks.